CeO2‐Nanorods‐Catalyzed Protoboration of Alkenes and Alkynes with Bis(pinacolato)diboron. Issue 4 (17th February 2023) - Bhawar, Ramesh; Saini, Suresh; Nagaraju, D. H.; Bose, Shubhankar Kumar
Abstract: The protoboration of alkenes and alkynes with B2 pin2 (pin=OCMe2 CMe2 O) using a heterogeneous CeO2 nanorods catalyst has been developed to afford the corresponding alkyl and vinyl boronate esters in 41–99% yield under mild reaction conditions. A series of aromatic and aliphatic alkenes and alkynes with synthetically important functional groups were well tolerated. In both the systems, the catalyst could be reused for up to six runs without significant loss in activity. Stoichiometric reactions revealed that the protoboration may proceed through the in situ formed catalytically active boryl species. Abstract :